2022
DOI: 10.1029/2022jd037236
|View full text |Cite
|
Sign up to set email alerts
|

Lightning Over Central Canada: Skill Assessment for Various Land‐Atmosphere Model Configurations and Lightning Indices Over a Boreal Study Area

Abstract: The boreal zone consists of a mosaic of different land cover types, mainly forests and peatlands, both storing large amounts of carbon (Scharlemann et al., 2014;Turetsky et al., 2015). One of the natural features shaping the boreal landscape is wildfire (Bowman et al., 2009). Several studies indicate that lightning is the major source of ignition of wildfires in the boreal zone (Turetsky et al., 2015). It is proposed that lightning may increase due to global warming (Y.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 95 publications
(193 reference statements)
2
4
0
Order By: Relevance
“…For all cases, LPI, LTI, and CAPE × P show high POD but a rather low SR, in agreement with the results of Mortelmans et al. (2023) for the skill assessment of LPI. The high bias of LPI, LTI, and CAPE × P can explain both the higher POD and the lower SR, which based on Equations and , it can be concluded that the model is simulating both more false alarms and more correctly predicted events.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…For all cases, LPI, LTI, and CAPE × P show high POD but a rather low SR, in agreement with the results of Mortelmans et al. (2023) for the skill assessment of LPI. The high bias of LPI, LTI, and CAPE × P can explain both the higher POD and the lower SR, which based on Equations and , it can be concluded that the model is simulating both more false alarms and more correctly predicted events.…”
Section: Resultssupporting
confidence: 91%
“…The high bias (>1) of LPI for Cases 1, 5, 6, and 7, LTI for Cases 1, 2, 5, 6, and 7, and CAPE × P for all cases indicate that more lightning flashes are predicted than the observation. For all cases, LPI, LTI, and CAPE × P show high POD but a rather low SR, in agreement with the results of Mortelmans et al (2023) for the skill assessment of LPI. The high bias of LPI, LTI, and CAPE × P can explain both the higher POD and the lower SR, which based on Equations 6, 8 and 9, it can be concluded that the model is simulating both more false alarms and more correctly predicted events.…”
Section: Predictive Performance Analysissupporting
confidence: 86%
See 2 more Smart Citations
“…Furthermore, the lightning potential index (LPI) and the index of potential electrical energy index (EP) have been introduced into convection-permitting regional climate models, which integrate the dynamics and microphysics factors to predict lightning activity associated with thunderstorms [8,42,43]. However, Mortelmans et al [44] pointed out that there is no single best method to predict lightning, but a finer model resolution improves the accuracy of the models. Different numerical models on a global scale can predict a wide range and long periods of lightning activity and its change.…”
Section: Introductionmentioning
confidence: 99%